Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work—Definitions, Dimensions, and Forms - Marisol Sandoval; Christian Fuchs; Jernej A. Prodnik; Sebastian Sevignani; Thomas Allmer (tripleC: Communication, Capitalism & Critique)
In 1845, Karl Marx (1845, 571) formulated the 11th Feuerbach Thesis: “The philosophers have only interpreted the world in various ways; the point is to change it.” Today, interpreting the world has become an important form of labour that is expressed on and with the help of digital media. In this context it has become common to talk about digital labour and virtual work. Yet the changes that digital, social, and mobile media bring about in the world of labour and work have thus far only been little theoretically interpreted. In order to change the information society for the better, we first have to interpret digital labour with the help of critical theories. Social theorists of the world from different fields, backgrounds, interdisciplines, transdisciplines, and disciplines have to unite for this collective philosophical task.